2020
DOI: 10.14710/ik.ijms.25.1.31-38
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Von Bertalanfy Growth, Allometric, Condition Index And Mortality of Periophthalmus barbarus in Mangrove and Probiotics Conservation Area (KKMB), Tarakan, North Kalimantan

Abstract: The Mudskipper (P. barbarus) lives in intertidal mud flats and it becomes an indicator of water quality. The transformation of construction and water pollution in this area is important to investigate due to interaction of fishery industry, home residence, and market area surrounding areas. The aim of this research was to analyze the characteristic of Von Bertalanffy growth, allometric, condition index, and mortality of the P. barbarus in KKMB, Tarakan city. The research was designed by using descriptive quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Similarly, Sunarni et al (2019) also found that female B. pectinirostris has positive allometric growth patterns with determination coefficient value of (R 2 = 0.9796-0.9784), where there was a strong correlation between the length and the weight of B. pectinirostris. Positive allometric growth of mudskipper was also found in male P. barbarous (Indarjo et al 2020), P. argentilineatus and P. spilotus (Khaironizam and Norma-Rashid 2002), and P. crysospilos (Abdullah and Zain 2019). However, the determination coefficient value of (R 2 = 0.3217) ( Table 5 and Figure 3) indicated that the length-weight relationship of P. malaccencis was very weak.…”
Section: Length-weight Relationship Of Mudskippermentioning
confidence: 94%
See 1 more Smart Citation
“…Similarly, Sunarni et al (2019) also found that female B. pectinirostris has positive allometric growth patterns with determination coefficient value of (R 2 = 0.9796-0.9784), where there was a strong correlation between the length and the weight of B. pectinirostris. Positive allometric growth of mudskipper was also found in male P. barbarous (Indarjo et al 2020), P. argentilineatus and P. spilotus (Khaironizam and Norma-Rashid 2002), and P. crysospilos (Abdullah and Zain 2019). However, the determination coefficient value of (R 2 = 0.3217) ( Table 5 and Figure 3) indicated that the length-weight relationship of P. malaccencis was very weak.…”
Section: Length-weight Relationship Of Mudskippermentioning
confidence: 94%
“…Interestingly, Periophthalmus is the only genus of mudskipper found in this area. According to Indarjo et al (2020) and Ansari et al (2014), the mudskipper from the genus Periophthalmus is endemic to the mangrove area, and not found in many places. This means that the mangrove area in the Kairatu beach is an endemic area for the genus Periophthalmus.…”
Section: Species Of Mudskippermentioning
confidence: 99%
“…According to Firdaus and Salim, (2013); Gazali Salim, (2015); Salim and Kelen, (2018); Indarjo et al, (2020); Firdaus et al (2020), the regression line in Figure 1 and 2 explains that to get the maximum growth (L∞) and the speed of growth coefficient based on the regression equation y = a + bx using the formula of Sparre and Seibren (1999) that is the average length-model value (-a / b) is used to assess the asymptotic length (L () using the linear regression method, while the growth coefficient (K) is -b. Correlation values obtained in the regression equation are used to analyze two different variables between the total length and total weight of layur fish (L. savala) using correlation criteria based on (Sarwono, 2006).…”
Section: Variable Absolute Growthmentioning
confidence: 99%
“…The Ŵ was estimated from the logarithmic transformed of the allometric growth formula: Log W=Log a + b Log L Condition index of the fish was categorized into five categories i.e. very thin (Kn=0.01-0.50), thin (Kn=0.51-0.99), ideal (kn=1.0), fat (kn=1.01-1.50), and very fat (kn>1.50) (Firdaus and Salim 2011;Salim 2013;Salim 2015;Firdaus et al 2018;Firdaus et al 2020;Indarjo et al 2020a;Indarjo et al 2020b;Indarjo et al 2020c).…”
Section: Condition Factormentioning
confidence: 99%